Optimization of 10nm Bi-GFET Device for higher ION/IOFF ratio using Taguchi Method - Roslan A.F.; Kaharudin K.E.; Salehuddin F.; Zain A.S.M.; Ahmad I.; Faizah Z.A.N.; Hazura H.; Hanim A.R.; Idris S.K.; Zaiton A.M.; Mohamad N.R.; Hamid A.M.A. (Institute of Physics Publishing, 2023)
Analysis of variance (ANOVA); Field effect transistors; Graphene transistors; Ion implantation; Ions; Taguchi methods; Bilayer Graphene; Dominant process; Halo implants; Implant energy; L9 orthogonal arrays; Parameter setting; Process parameters; Statistical modeling; Signal to noise ratio